Preliminary Analysis of ROV AF-150114 Movement Using CFD Method (Comutional Fluid Dynamics) - Shanty Manullang; Agus Setiawan; Rizky Irvana; Mercy Patanda (International Journal of Marine Engineering Innovation and Research, 2023)
This research was carried out with the aim of measuring the effect of the body on the fluid flow that occurs around it and measuring the stress that occurs in the ROV AF-150114 design. The research method uses software with a CFD model approach to analyze the stress that occurs in the designs made. In general, there are three stages that must be passed in a CFD simulation: Pre-processing. Solving and post-processing. What is calculated is the velocity, viscosity and pressure of the water flow around the ROV body. The results obtained show that the balance of the ROV body greatly affects the ability to dive and maneuver during maneuvers. The highest pressure/pressure for fluid flow occurs at the ROV AF-150114 speed of 2.5 m/s with a value 39,825 Pa and the value of viscosity is 10,860 Nm/s2. ROV AF-150114 movement test results found that the experiment has a faster movement time speed than the calculation.